Chemical Synthesis of Biologically Active Monoglycosylated GM2‐Activator Protein Analogue Using N‐Sulfanylethylanilide Peptide1. Issue 30 (13th June 2013) - Sato, Kohei; Shigenaga, Akira; Kitakaze, Keisuke; Sakamoto, Ken; Tsuji, Daisuke; Itoh, Kohji; Otaka, Akira
<x xml:space="preserve">Abstract</x> Going to SEA(lide): Total chemical synthesis of a 162‐residue glycoprotein analogue of the monoglycosylated human GM2‐activator protein (GM2AP) was achieved. Key steps were the use of N‐sulfanylethylanilide (SEAlide) peptides in the kinetic chemical ligation synthesis of a large peptide fragment, and a convergent native chemical ligation for final fragment assembly.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>